THE EFFECT OF THE PANCASILA LERNER PROFILE REINFORCEMENT PROJECT ON LEARNER CREATIVITY - Luluk Wisniwati; Evitasari, Atika Dwi; Palupi, Yulia (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2025)
This study aims determine the influence of the Pancasila student profile strengthening project on student’s creativity. The research uses Ex post facto quantitative method with regression analysis. The population and sample in this study are students of SD N 2 Sentolo With a sample of 22 students in class V determined using the  purposive sampling technique. Data collection was taken through questionnaires and documentation. The collected data were analyzed using a simple linear regression test. The results of this study show that there is a positive and significant influence between the project to strengthen the Pancasila student profile on the creativity of students at SD N 2 Sentolo (p<0.05) with a determination coefficient of 0.419. This can be proven by a simple linear regression equation: Y= 77.644+0.142X stated that H1 is accepted H0 rejected. Therefore, it can be concluded that there is an influence of the Pancasila student profile strengthening project on the creativity.